Industrial relations in South Africa : labour laws, labour institutions and political disillusionment - Hobbs, Jacklynne; Horne, Renee (London : SAGE Publications Ltd, 2017)
In 2014, South Africa experienced its longest and costliest strike ever: a five-month stoppage in the platinum sector that cast doubt on the institutions and culture of the countrys labour relations framework. After the strike came to an end in late June, the National Economic Development and Labour Council (Nedlac) convened a meeting to discuss ways of preventing further violent and protracted industrial action. Among the questions confronting delegates at this gathering was whether labour unrest could be addressed by altering the laws and institutions regulating strikes. Or would any such reforms prove largely futile in the absence of political and economic change?
Originally published in Hobbs, R., & Horne, R. (2015). Industrial relations in South Africa: Labour laws, labour institutions and political disillusionment. WBS-2015-6. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Labor laws and legislation -- South Africa; Conflict management -- South Africa